2020
DOI: 10.1007/s10549-020-05611-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of contralateral breast cancer: external validation of risk calculators in 20 international cohorts

Abstract: Background Three tools are currently available to predict the risk of contralateral breast cancer (CBC). We aimed to compare the performance of the Manchester formula, CBCrisk, and PredictCBC in patients with invasive breast cancer (BC). Methods We analyzed data of 132,756 patients (4682 CBC) from 20 international studies with a median follow-up of 8.8 years. Prediction performance included discrimination, quantified as a time-dependent Area-Under-the-Curve (AUC) at 5 and 10 years after diagnosis of primary BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Currently available CBC models, such as CBCrisk and the Manchester formula, show only moderate discrimination [51]. In addition, the Manchester formula has been shown to systematically overestimate CBC risk [51].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available CBC models, such as CBCrisk and the Manchester formula, show only moderate discrimination [51]. In addition, the Manchester formula has been shown to systematically overestimate CBC risk [51].…”
Section: Discussionmentioning
confidence: 99%
“…These models calculate an individual's risk of contralateral breast cancer in different ways using patient and tumor characteristics such as age at first primary breast cancer diagnosis, family history, ER status, breast density, first breast cancer type, and adjuvant treatments. However, these models are not widely used yet [37]. Giardiello et al [37], who used individual patient data from a number of studies with a long follow-up, evaluated the accuracy of the three models.…”
Section: Risk Of Contralateral Breast Cancermentioning
confidence: 99%
“…However, these models are not widely used yet [37]. Giardiello et al [37], who used individual patient data from a number of studies with a long follow-up, evaluated the accuracy of the three models. They found only moderate discrimination of all three models and considerable heterogeneity between studies, and concluded that careful re-calibration is required before these models could be used in clinical decision-making [37].…”
Section: Risk Of Contralateral Breast Cancermentioning
confidence: 99%
“…The results of our study can be used to further personalise CBC risk management. In combination with other factors that influence CBC risk [ 4 ], we aim to identify patients at high and low risk of CBC [ 27 , 28 ]. Based on the results of this study, the frequency of screening and choices regarding risk-reducing surgeries cannot be tailored to the different risk-profiles yet, though this would be the subsequent goal.…”
Section: Discussionmentioning
confidence: 99%